A naphthalene diimide G-quadruplex ligand inhibits cell growth and down-regulates BCL-2 expression in an imatinib-resistant gastrointestinal cancer cell line. Issue 11 (15th July 2018) - Gunaratnam, Mekala; Collie, Gavin W.; Reszka, Anthony P.; Todd, Alan K.; Parkinson, Gary N.; Neidle, Stephen
Graphical abstract: Abstract: Gastro-intestinal tumours (GISTs) are driven by aberrant expression of the c-KIT oncoprotein. They can be effectively treated by the kinase inhibitor imatinib, which locks the c-KIT kinase domain into an inactive conformation. However resistance to imatinib, driven by active-site mutations, is a recurrent clinical challenge, which has been only partly met by the subsequent development of second and third-generation c-KIT inhibitors. It is reported here that a tetra-substituted naphthalene diimide derivative, which is a micromolar inhibitor of cell growth in a wild-type patient-derived GIST cell line, has a sub-micromolar activity in two distinct patient-derived imatinib-resistant cell lines. The compound has been previously shown to down-regulate expression of the c-KIT protein in a wild-type GIST cell line. It does not affect c-KIT protein expression in a resistant cell line to the same extent, whereas it profoundly down-regulates the expression of the anti-apoptopic protein BCL-2. It is proposed that the mechanism of action involves targeting quadruplex nucleic acid structures, and in particular those in the BCL-2 gene and its RNA transcript. The BCL-2 protein is up-regulated in the GIST-resistant cell line, and is strongly down-regulated after treatment. The compound strongly stabilises a range of G-quadruplexes including a DNA one from the BCL-2 promoter and an RNA quadruplex from its 5′-UTR region. A reporter assay construct incorporating the 5′-UTR quadruplex sequence demonstrates down-regulation of BCL-2 expression.